1983
DOI: 10.1037/0278-7393.9.4.626
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of hypnotic and nonhypnotic forgetting.

Abstract: Subjects participated in two experimental sessions designed to study laboratory-induced amnesia, one using a standard hypnosis paradigm and one using a non-hypnotic directed-forgetting paradigm. Two independent sources of variation were derived from the hypnotic amnesia data: retrieval inhibition and inhibition release. In the nonhypnotic directed-forgetting procedure, some items were cued to be forgotten shortly after presentation and some were cued to be remembered. At test, the subjects were asked to recall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
0
24
1
Order By: Relevance
“…Geisel- man, Bjork, and Fishman (1983) found that a forget cue can have a deleterious effect on items that subjects have no intent to remember in any case, and that the pattern of recall for F items appears to be disrupted. Furthermore, Geiselman, MacKinnon, et al (1983) found a correspondence between individual differences in hypnotic amnesia (ascribed to retrieval inhibition) and individual differences in waking intentional forgetting. The present results complement the previous word in that unrecalled F items appear to be qualitatively different from unrecalled R items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geisel- man, Bjork, and Fishman (1983) found that a forget cue can have a deleterious effect on items that subjects have no intent to remember in any case, and that the pattern of recall for F items appears to be disrupted. Furthermore, Geiselman, MacKinnon, et al (1983) found a correspondence between individual differences in hypnotic amnesia (ascribed to retrieval inhibition) and individual differences in waking intentional forgetting. The present results complement the previous word in that unrecalled F items appear to be qualitatively different from unrecalled R items.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when hypnosis is used, a forget instruction is effective for inhibiting recall when items have been well learned (Kihlstrom, 1977) and when the instruction is presented just before test. Furthermore, a countermand often reverts recall performance to a high level (Geiselman, MacKinnon, et al, 1983;Kihlstrom & Evans, 1976). It appears, therefore, that there are certain conditions in which retrieval inhibition can be manipulated near the time of item retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Two investigations largely failed to replicate the effect (Radtke & Spanos, 1981;St. Jean & Coe, 1981), although a more recent attempt was successful (Geiselman et al, 1983) More important, Radtke and Spanos (1981) offered a critique of the methodology employed in these studies, leading them to conclude that the temporal disorganization effect has not yet been convincingly demonstrated. Their critique focused on five points: (a) There was no assessment of the degree of initial learning, making it difficult to assess the degree of amnesia displayed by the subjects, (b) the memory task was somewhat ambiguous in that it may have been unclear to some subjects what they were supposed to be remembering, (c) the time period allotted for recall may have been too short, (d) there was no assessment of the recovery of memory, and of organization, after the amnesia was reversed, and (e) the rho-score statistic used to quantify temporal disorganization was unconventional and has certain undesirable psychometric properties-although other commentators have disagreed (Pellegnno & Huber, 1982).…”
mentioning
confidence: 99%
“…Inhibition, a theoretical mechanism analogous to neural inhibition, refers to a temporary deficiency in one's ability to retrieve material stored in memory. Retrieval inhibition has been suggested as the mechanism responsible for a number of forgetting phenomena, including post-hypnotic amnesia, directed forgetting (e.g., Geiselman et al, 1983; but see Kihlstrom, 1983;Kihlstrom & Barnhardt, 1993), retrieval induced forgetting, part-list cueing effects (e.g., , and memory suppression (e.g., Anderson & Green, 2001). In the Anderson and Green study, both associative interference and unlearning of the cue-target association were ruled out as the mechanisms underlying the observed retrieval impairment, providing strong support in this case for the existence of an inhibitory control mechanism inhibiting the unwanted memory itself.…”
Section: Theoretical Explanations For Blocked and Recovered Memoriesmentioning
confidence: 99%